Crop processing and early medieval settlement: the evidence for Bayvil, Pembrokeshire - Comeau, Rhiannon (Medieval Settlement Research, 2021)
A corn-drying kiln in west Wales with 5th- to 6th-century AD dates provides the starting point for an assessment of early medieval settlement and agricultural evidence. The corn-drying kiln, a feature often associated with estate centres, was discovered during the excavation of a Late Bronze Age ringfort, and lies in an area where excavation and field survey identify a dispersed pattern of enclosed settlements, some showing traces of use contemporary with the kiln. The relationship of the kiln contents to patterns of husbandry, notably infield-outfield agriculture and spring-sown cereals, is reviewed. Indications of the area’s probable focal zone status are noted, and it is suggested that, given the frequent use of corn-drying kilns for bulk-drying of processed crops for granary storage or milling, and for making malt for ale, the kiln may have been used to support food and/or drink production for large gatherings.